The capital agglomeration of the Republic of Korea as a fuzzy central place system - Em Pavel P. (Bulletin of Geography. Socio-Economic Series)
Explosive urbanization in the Republic of Korea from 1950 to 2010 marked by a growth in extensive urban agglomerations rendered unproductive the approach that was commonly used in the central place theory and which considered every element of the settlement system as a point in a homogeneous space. The paper suggests an alternative concept of fuzzy central place that makes possible the understanding of an internal heterogeneity in the distribution of central functions within the limits of urban agglomerations. This research was conducted using the example of the Capital agglomeration - the main element of the Republic of Korea’s urban settlement system. This “island” country, isolated by North Korea, has seen fantastic economic growth in the second half of the 20th century.